RFI and determination of celestial objects in the range of radio frequency wavelength / Ahmad Faizal Zadeli. - Zadeli, Ahmad Faizal (2010)
1000 years ago, nobody in the world know there are very crucial part at outer space that we can explore more.Today,Radio astronomy is an important subfield of astronomy that studies celestial objects in the range of radio frequency portion of the electromagnetic spectrum. It is important to identify radio frequency interference (RFI) in the observational window. Radio Frequency Interference (RFI) is disturbance that affects electrical circuit due to electromagnetic radiation emitted from an external source. The disturbance may interrupt, obstruct, or otherwise degrade or limit the effective performance of the circuit. In this project, two sites were choosed, Padang Kawad and Applied Science Faculty at block A. First we need to determined which site has minimum frequency of RFI.The result obtained showed the lowest RFI located at Applied Science Faculty at block A. After site was choose, we refer to MCMC data and ITU data to identified celestial object that can be observed with lowest RFI we obtained at this site is -100.61 db and the object that can be observed is Jupiter.